Brain-gut interactions in obesity 1 - Pan, Weihong (Henry Stewart Talks, 2019)
Blood-brain barrier (BBB) permeation of ingestive peptides, Leptin as a major example, Receptor-mediated transport, Modulation by feeding status, Activation of other systems such as that of urocortin, Multi-modality, including specific transport and simple diffusion, Direct actions and generation of secondary mediators at the level of BBB endothelia, The BBB, BCSFB, and circumventricular organs (CVOs)